Motives, Positions, and Strategies of State-Owned Islamic Banks after The Merger - Nugroho Heri Pramono; Fika Azmi (Business Finance Analyst Co., 2023)
The purpose of this study is to find out and analyze the position of Islamic banks resulting from the merger between conventional banks and Islamic banks in Indonesia and what strategic steps are taken by these Islamic banks. The research method used in this research is a descriptive qualitative approach with the case study method. Data collection was carried out by in-depth interviews, direct observation of informants, namely the Director of KNEKS, the managers of the merged Islamic banks (Bank Syariah Mandiri, Bank BRI Syariah, and Bank BNI Syariah), as well as the Ministry of BUMN. Data collection was also carried out secondary, namely through literature studies from journals, text books, and websites as well as other literature. Data analysis used in this research is internal strategic analysis (Internal Factor Analysis Strategic / IFAS) and external strategic analysis (External Factor Analysis Strategic / EFAS), internal external matrix analysis (IE matrix), and SWOT matrix analysis. The results of the study show that Bank Syariah Indonesia is in quadrant 1 which means it is in a condition of growth and can be developed. Based on the results of the analysis of internal and external differences, Bank Syariah Indonesia is in a position of stable growth and a conglomerate diversification strategy. So that Islamic Banks can diversify products for expansion to all lines of business and overseas.